Biomaterial–tight junction interaction and potential impacts. Issue 41 (31st July 2019) - Han, Xiangfei; Zhang, Ershuai; Shi, Yuanjie; Song, Boyi; Du, Hong; Cao, Zhiqiang
Abstract : Biomaterial–tight junction (TJ) interactions: analyses of the TJ structure and natural modulation, interaction mechanism, potential impact and measuring methods. Abstract : The active pharmaceutical ingredients (APIs) have to cross the natural barriers and get into the blood to impart the pharmacological effects. The tight junctions (TJs) between the epithelial cells serve as the major selectively permeable barriers and control the paracellular transport of the majority of hydrophilic drugs, in particular, peptides and proteins. TJs perfectly balance the targeted transport and the exclusion of other unexpected pathogens under the normal conditions. Many biomaterials have shown the capability to open the TJs and improve the oral bioavailability and targeting efficacy of the APIs. Nevertheless, there is limited understanding of the biomaterial–TJ interactions. The opening of the TJs further poses the risk of autoimmune diseases and infections. This review article summarizes the most updated literature and presents insights into the TJ structure, the biomaterial–TJ interaction mechanism, the benefits and drawbacks of TJ disruption, and methods for evaluating such interactions.